EFFECT OF SUPPLEMENTATION OF F100 BISCUITS MODIFIED WITH MORINGA OLEIFERA FLOUR SUBSTITUTION ON NUTRITIONAL STATUS OF UNDER-FIVE CHILDREN WITH MALNUTRITION IN KENDARI CITY INDONESIA - Mayangsari, Riska; Rasmiati, Ketut (Public Health of Indonesia, 2020)
Background: Malnutrition is a condition of severe nutritional deficiency caused by an insufficient intake of energy and protein from daily food consumption. The most lethal impacts are declined IQ score, decreased cognitive development, and diminished sensory integration, which could harm the life of the children and resulted in the loss of the national youth generation. One effort to overcome this problem is to develop a diet alternative using F100 materials substituted from kelor (Moringa Oleifera) flour as the main ingredient and reform it into edible biscuits. Kelor leaves contain multiple micronutrient elements that are essential for children and have been proven to increase the nutritional status of children with malnutrition.Objective: This research aims to identify the effect of the supplementation of F100 biscuits modified with kelor flour substitution on the nutritional status of under-five children with malnutrition.Methods: This was a pre-experimental study conducted in Kendari city Indonesia from May-June 2019. Twenty children were included and given modified biscuits on a scale of 100 gm per day for six consecutive weeks. Data were analyzed using dependent and independent sample t-test.Results: There was a significant effect of the supplementation of F100 modified biscuits on the nutritional status of under-five children with malnutrition (p = 0.002).Conclusion: The F100 supplementation modified with kelor flour substitution biscuits has been proven to be effective in increasing the nutritional status of under-five children with malnutrition.